Quantitative study of stiffness in the knee joint. Issue 4 (August 1975) - Such, C H; Unsworth, A; Wright, V; Dowson, D
Abstract : Data from a knee arthrograph, which imparts a passive sinusoidal motion to the joint and measures the resistive torque and displacement, have been shown to be reproducible. Tests carried out on joints (from 49 males, 21 females) showed that the energy loss per cycle of the joint increased with age for both sexes but the peak to peak torque (elastic stiffness) did not vary with age. Muscle bulk had a large influence on the stiffness (both dissipative and elastic) of the knee as did the size of the joint itself. Women's knee joints exhibited lower values of dissipative energy loss and peak to peak torque than men's for all ages and sizes of joints.